The cottage on Pelican Bay - Jackson, Brenda (Brenda Streater) (Jackson, Brenda (Brenda Streater). Catalina Cove, 2024)
Returning to the small Louisiana town of Catalina Cove to care for his aging parents, Saint is shocked when he comes face to face with "Angel," the no-strings woman of his dreams with whom he had an unforgettable one-night stand, discovering her brother is his new boss.